1994
DOI: 10.1007/bf02249330
|View full text |Cite
|
Sign up to set email alerts
|

The subjective, behavioral and cognitive effects of subanesthetic concentrations of isoflurane and nitrous oxide in healthy volunteers

Abstract: A prospective, crossover, double-blind trial was conducted in nine healthy volunteers in which the subjective, psychomotor and memory effects of isoflurane (0.0, 0.3 and 0.6%) and nitrous oxide (N2O) (0, 20 and 40%) were examined. Dependent measures included visual analog scales and a standardized drug effects inventory (subjective effects), reaction time and eye-hand coordination (e.g., psychomotor performance), and immediate and delayed free recall (memory). There were some similarities in subjective effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…One study using a similar concentration of nitrous oxide to that reported here, also reported nonsignificant increases in reaction time. 23 While other studies have revealed significant increases in reaction time, such effects were dose-dependent, and reaction time slowing may only be seen at the highest doses. 17 On the other cognitive measures, nitrous oxide inhalation led to mild performance impairments, which did not differ significantly from performance in the control sessions.…”
Section: Discussionmentioning
confidence: 91%
“…One study using a similar concentration of nitrous oxide to that reported here, also reported nonsignificant increases in reaction time. 23 While other studies have revealed significant increases in reaction time, such effects were dose-dependent, and reaction time slowing may only be seen at the highest doses. 17 On the other cognitive measures, nitrous oxide inhalation led to mild performance impairments, which did not differ significantly from performance in the control sessions.…”
Section: Discussionmentioning
confidence: 91%
“…An animal study examining the behavioural and electrophysiologic effects of four anaesthetic agents infused into the cerebral ventricles of conscious rats demonstrated depressed olfactory responses following propofol and fentanyl, with propofol producing the strongest effect [2]. Another study in humans assessing [15]. Standard brain and sinus imaging studies (CT scan, MRI) of patients with loss of smell are usually normal except for a relatively small number of cases with nasal pathology, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…55 Sub-sedative doses of isoflurane (0.3%) and nitrous oxide (20%) also impaired immediate and delayed word recall. 56 Memory for emotional encounters was blocked by sub-anesthetic concentrations of sevoflurane (0.25%), desflurane (1.5-2 times MAC-awake), and propofol (1.5-2 times MAC-awake). 57,58 At MAC-equivalent concentrations, some anesthetics are more effective than others at preventing memory.…”
Section: Blockade Of Memory By General Anesthetics In Humans and Labomentioning
confidence: 96%